Aftermath - Armstrong, Kelley (New York : Crown, 2018)
"Three years after losing her brother Luka in a school shooting, Skye Gilchrist is moving home. But theres no sympathy for Skye and her family because Luka wasnt a victim: he was a shooter. Jesse Mandal knows all too well that the scars of the past dont heal easily. The shooting cost Jesse his brother and his best friend--Skye. Ripped apart by tragedy, Jesse and Skye cant resist reopening the mysteries of their past"--
HL590
Keywords: School shootings; Juvenile fiction; Brothers -- Death; Juvenile fiction; High school students; Juvenile fiction; Best friends; Juvenile fiction; Mass murder investigation; Juvenile fiction; School shootings -- Fiction; Brothers -- Death; Fiction; High school students -- Fiction; Best friends -- Fiction; Mass murder investigation -- Fiction; School shootings -- Fiction; Brothers -- Death; Fiction; High school students -- Fiction; Best friends; Fiction; Mass murder investigation -- Fiction